2020
DOI: 10.3390/cells9020292
|View full text |Cite
|
Sign up to set email alerts
|

The LisH Domain-Containing N-Terminal Fragment is Important for the Localization, Dimerization, and Stability of Katnal2 in Tetrahymena

Abstract: Katanin-like 2 protein (Katnal2) orthologs have a tripartite domain organization. Two highly conserved regions, an N-terminal LisH (Lis-homology) domain and a C-terminal AAA catalytic domain, are separated by a less conserved linker. The AAA domain of Katnal2 shares the highest amino acid sequence homology with the AAA domain of the canonical katanin p60. Katnal2 orthologs are present in a wide range of eukaryotes, from protists to humans. In the ciliate Tetrahymena thermophila, a Katnal2 ortholog, Kat2, co-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…KATNAL2 is a member of the paralogue of katanin, which is a type of microtubule‐severing protein and critical regulator of microtubule dynamics in multiple species 30 . The generation of mature germ cells, including the sperm and oocyte, is tightly dependent on complex and precise regulation of meiosis in the primordial germ cells, in which microtubule severing and spindle assembly are indispensable 31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…KATNAL2 is a member of the paralogue of katanin, which is a type of microtubule‐severing protein and critical regulator of microtubule dynamics in multiple species 30 . The generation of mature germ cells, including the sperm and oocyte, is tightly dependent on complex and precise regulation of meiosis in the primordial germ cells, in which microtubule severing and spindle assembly are indispensable 31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in KATNAL2, the MIT domain of KATNA1 and KATNAL1 is replaced by a lissencephaly homology (LisH) domain ( Figure 1 ; Cheung et al, 2016 ; Ververis et al, 2016 ). In the ciliate Tetrahymena thermophila , the LisH domain of the katanin homolog Kat2 is important for its stability, self-dimerization, and localization to the basal body and ciliary axoneme ( Joachimiak et al, 2020 ). Although the functional importance of the KATNAL2 LisH domain has yet to be determined in vertebrates, it is likely to regulate KATNAL2 localization, stabilization, self-association, and association with other proteins.…”
Section: Katanin Subunit Conservation and Domain Organizationmentioning
confidence: 99%
“…The function of katanin on the cilia has been widely studied using unicellular eukaryotes; for example, research investigating Tetrahymena and Chlamydomonas A- and B-subunit homologs has informed on katanin activity and localization on ciliary structures ( Waclawek et al, 2017 ; Joachimiak et al, 2020 ), as well as the biogenesis of motile cilia ( Sharma et al, 2007 ). Several recent studies have implicated katanin in the assembly, disassembly, and function of cilia in vertebrates ( Hu et al, 2014 ; Willsey et al, 2018 ; Mirvis et al, 2019 ).…”
Section: Katanin In Ciliary Homeostasis and Developmentmentioning
confidence: 99%
“…Structural analysis showed that HOS15 comprises four major motifs: the LisH motif, WD-40 domain, F-box-like motif, and DWD motif. The LisH motif is involved in protein dimerization (Choi et al, 2008;Joachimiak et al, 2020). The WD-40 motif is important for protein-protein interactions (Xu and Min, 2011).…”
Section: Introductionmentioning
confidence: 99%